Julius Eastman: The Sonority of Blackness Otherwise - Jean-Francois, Isaac (Current Musicology, 2020)
This paper analyzes the life and work of Julius Eastman (1940–1990), namely his 1980 Northwestern Concert Series and Grammy-nominated Eight Songs for A Mad King (1973) alongside anti-black state violence in the United States as sites of black sonority made legible through and against, what Christina Sharpe calls, “the wake” of chattel slavery (2016). The mouth, stifled breath, and voice, I have argued, all persist through the reiterative scene of state-sanctioned violence against black and brown people. I am interested in the historicized phenomenology of sounds produced in radically different scenes of performance and murder. That is, the history of black and brown folx in America is, in part, produced out of, “[t]he ‘very dangerous evil’ of slavery and the ‘agonizing groans of suffering humanity’ [that] had been made music” (Saidiya Hartman 1997, 17). The paper departs from the scene of black sonority processed under duress to query: what are the effects of racialized aesthetic production, as evident in the Eastman’s musical groan or shriek that is eerily similar to the foreclosure of black breath, that emerge at the impasse between virtuosic sound and historicized dispossession? I offer an alternative reading of sound production by way of what Ashon T. Crawley who crafts a hermeneutics of the sound of blackness offers a consideration of black sound making “otherwise.” The breath of black and brown folx that persists in spite of antiblackness must flow into putatively apolitical disciplines like Musicology in an effort to render (il)legible life sonorous otherwise.